Assessment of the Barriers to the Development of Health Tourism in Yazd Province, Iran - Fatemeh Azizi; Shamsalsadat Zahedi (مدیریت اطلاعات سلامت, 2016)
Introduction: Today, health tourism is an important and growing phenomenon in the world. Iran has been one of the most active centers of health tourism in the region. Due to the important role of the health tourism industry in the global economy and the capabilities of Yazd Province, Iran, in this industry, the purpose of this study was to identify and evaluate barriers to the development of health tourism in this province.